Africa rising how 900 million African consumers offer more than you think - Mahajan, Vijay (Upper Saddle River Wharton School Pub, 2009)
With more than 900 million consumers, the continent of Africa is one of the world?s fastest growing markets. In Africa Rising, renowned global business consultant Vijay Mahajan reveals this remarkable marketplace as a continent with massive needs and surprising buying power. Crossing thousands of miles across the continent, he shares the lessons that Africa?s businesses have learned about succeeding on the continent...shows how global companies are succeeding despite Africa?s unique political, economic, and resource challenges...introduces local entrepreneurs and foreign investors who are building a remarkable spectrum of profitable and sustainable business opportunities even in the most challenging locations...reveals how India and China are staking out huge positions throughout Africa...and shows the power of the diaspora in driving investment and development. Recognize that Africa is richer than you think Africa is richer than India on the basis of gross national income (GNI) per capita, and a dozen African countries have a higher GNI per capita than China. Aim for Africa Two Opportunities exist in all parts of the market, particularly the 400 million people in the middle of the market. Find opportunities to organize the market From retailing to cell phones to banking, companies are succeeding by building infrastructure. Develop strategies for the most youthful market in the world Companies are recognizing opportunities from diapers to music to medicine in a market growing younger every day. Understand that Africa is not a ?media dark? continent From Nollywood to satellite to broadband, media is exploding on the continent. Recognize the hidden strength of the African diaspora The African diaspora brings resources and knowledge to African development and expands the African opportunity beyond the continent. Build Ubuntu markets Create profitable businesses, sustainable growth, and social organizations by meeting basic human needs.
Includes bibliographical references (p. 221-237)
Keywords: Investments, Foreign-Africa. International business enterprises -Africa. Africa-Commerce. Africa-Economic conditions